2021
DOI: 10.3389/fendo.2021.671566
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Therapeutic Role of MSCs in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is one of the most common diabetes mellitus (DM) microvascular complications, which always ends with end-stage renal disease (ESRD). Up to now, as the treatment of DN in clinic is still complicated, ESRD has become the main cause of death in diabetic patients. Mesenchymal stem cells (MSCs), with multi-differentiation potential and paracrine function, have attracted considerable attention in cell therapy recently. Increasing studies concerning the mechanisms and therapeutic effect of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 129 publications
(129 reference statements)
0
18
0
Order By: Relevance
“…An increasing body of evidence suggests that MSC-based therapy can improve patient outcomes in DKD treatment, including decreasing proteinuria, improving renal function, and alleviating renal fibrosis. [28][29][30] At present, there is ample evidence that MSCs mainly exert therapeutic effects through exosomes-mediated paracrine mechanisms. 31 It has been suggested that MSC-exos can fix cisplatin-induced AKI in rats and NRK-52E cell injury by ameliorating oxidative stress and cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggests that MSC-based therapy can improve patient outcomes in DKD treatment, including decreasing proteinuria, improving renal function, and alleviating renal fibrosis. [28][29][30] At present, there is ample evidence that MSCs mainly exert therapeutic effects through exosomes-mediated paracrine mechanisms. 31 It has been suggested that MSC-exos can fix cisplatin-induced AKI in rats and NRK-52E cell injury by ameliorating oxidative stress and cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the clinical treatment is to slow down DN progression by administering drugs that improve blood pressure or blood glucose levels. Once DN progresses to irreversible stages, alternative treatments such as hemodialysis are inevitable 77 . Li et al 78 reported that mouse umbilical cord MSCs (MUC-MSCs) blocked transforming growth factor-β(TGF-β)-triggered myofibroblast transdifferentiation through paracrine sEVs, inhibited PI3K/Akt and mitogen-activated protein kinase (MAPK) signaling-mediated mesangial cell proliferation, increased matrix metalloproteinase levels in mesangial cells, and reduced renal fibrosis in a DN mouse model.…”
Section: Msc-sevs In Kidney Diseasementioning
confidence: 99%
“…However, the incidence of end-stage renal disease remains high. BMSCs-Exos have been proven to participate in slowing down the progression of DN by controlling hyperglycemia and protecting kidney function [ 141 ]. In addition, exosomes derived from ADSCs and hucMSCs have also been confirmed to be used for the treatment of DN [ 146 , 147 ] ( Table 2 ).…”
Section: Evs In Aging-related Diseasesmentioning
confidence: 99%
“…Diabetic Nephropathy. Diabetic nephropathy (DN) is one of the microvascular complications of DM, which causes end-stage renal disease [141]. Its clinical diagnosis mainly depends on the presence of proteinuria and the estimated decrease in the glomerular filtration rate [142].…”
Section: Roles Of Evs In Dm and Itsmentioning
confidence: 99%